Developing a Scale Measuring of Spontaneous Behaviors in the Workplace - Al-Hakim, Laith Ali Yousif (International Journal of Psychosocial Rehabilitation, 2020)
During recent years, research on spontaneous behaviors has been increasing but there is still need to develop and validate an instrument to measure this variable. Therefore, the aim of this study is to propose a scale to measure spontaneous behaviors. Based on the content analyses researchers developed a questionnaire. The sample consisted of 200 employees who work in the Al-Kafeel Specialist Hospital in the holy city of Karbala. The exploratory analysis identified five dimensions of this variable with (25) items.